Effects of Social Support by a Dog on Stress Modulation in Male Children with Insecure Attachment - Beetz, Andrea; Julius, Henri; Turner, Dennis; Kotrschal, Kurt (Frontiers in Psychology, 2012)
Up to 90% of children with special education needs and about 40% of children in the general population show insecure or disorganized attachment patterns, which are linked to a diminished ability to use social support by others for the regulation of stress. The aim of the study was to investigate if children with insecure-avoidant/disorganized attachment can profit more from social support by a dog compared to a friendly human during a stressful task. We investigated 47 male children (age 7-11) with insecure-avoidant or disorganized attachment. Social stress was elicited via the Trier Social Stress Test for Children (TSST-C). For one group of children a friendly therapy-dog (N=24) was present, for one control group a friendly human (N=10) and for the other control group a toy dog (N=13). Stress levels were measured via salivary cortisol before, during, and after the TSST-C and subjective reports. The physiological stress response was significantly lower in the dog condition in comparison to the two other support conditions. Cortisol levels correlated negatively with the amount of physical contact between child and dog. We conclude that male children with insecure-avoidant or disorganized attachment profit more from the presence of a therapy-dog than of a friendly human under social stress. Our findings support the assumption that the increasing practice of animal-assisted education is reasonable and that dogs can be helpful assistants in education/special education, since stress interferes with learning and performance in students.